Air pollution, well-being, and quality of life in Latin America: a systematic review - Álvarez, Boris; Boso, Àlex; Vallejos-Romero, Arturo (Iberoamerican Journal of Development Studies, 2023)
The aim of this review was to describe the effects of air pollution on well-being and quality of life in Latin American countries, following the systematic methods of the PRISMA-P guidelines. A systematic search of empirical studies published in Web of Science (WoS), Scopus, Scielo and PubMed databases was performed. Thus 17 relevant studies published between 1986 and 2021 were identified: 16 with quantitative designs and 1 a qualitative design. The selected studies were grouped into three thematic approaches: mental health (41 %), negative emotions (35 %) and subjective well-being (24 %). The results indicate that air pollution influences various components of well-being, such as satisfaction with life, subjective well-being, perception of quality of life, symptoms of depression or anxiety, negative emotions such as anguish, annoyance, and frustration, among others. However, there were also multiple empirical gaps to be filled.